2022
DOI: 10.1128/spectrum.00366-22
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Lassa Fever Virus-Positive Rodents and Diversity of Infected Species Found during Human Lassa Fever Epidemics in Nigeria

Abstract: Our findings show the highest LASV positivity in small rodents ever recorded and the first direct detection of LASV in Tatera spp. Our findings also indicate the abundance of LASV-infected small rodents in houses, with probable interspecies transmission through vertical and horizontal coitus routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…The causative agent of this zoonotic acute VHF is a singlestranded ribonucleic acid (RNA) virus belonging to the Arenaviridae family. The major reservoir of Lassa virus is the multimammate rat of the genus Mastomys; also been discovered in other rodents [4][5][6][7]. It accounts for an estimated two million infections, 300,000-500,000 clinical infections, and 10,000 deaths yearly among inhabitants of the West African sub-region, where it remains endemic [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The causative agent of this zoonotic acute VHF is a singlestranded ribonucleic acid (RNA) virus belonging to the Arenaviridae family. The major reservoir of Lassa virus is the multimammate rat of the genus Mastomys; also been discovered in other rodents [4][5][6][7]. It accounts for an estimated two million infections, 300,000-500,000 clinical infections, and 10,000 deaths yearly among inhabitants of the West African sub-region, where it remains endemic [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Three microliters (3 µl) of the isolated RNA from each sample was then used for the detection of LASV nucleic acid using Superscript III Platinum SYBR Green one-step RT-qPCR kit (Life Technologies, CA, USA). Specific primers targeting the nucleoprotein (NP) gene on the S segment of the viral genome (LASV-NG-F – 5′ – YAC AGG GTC YTC TGG WCG ACC – 3′ and LASV-NG-R – 3′ – RAT GAT GCA RCT TGA CCC AAG – 3′), as previously described [ 7 , 21 ] were used. Each sample type was run in duplicate, and the average cycle threshold (Ct) value was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Serological and viral evidence of LASV infection have been found in other rodents such as roof rats ( Rattus rattus) and house mice ( Mus musculus) [ 6 , 7 , 11 ] . Specifically, Olayemi et al [ 6 ] found that the African wood mouse ( Hylomyscus pamfi) and the reddish-white mastomys ( Mastomys erythroleucus) were positive for LASV by PCR over several years at the same sites and are likely to be legitimate reservoirs and not simply incidental hosts.…”
Section: Introductionmentioning
confidence: 99%
“…The main host and reservoir of LASV is Mastomys natalensis , a rodent that lives near houses in rural villages. Capture surveys have detected LASV in 3.2–52% of rodents 2 , 5 . LASV is transmitted to humans through aerosolization of viral particles from rodent excrement.…”
Section: Mainmentioning
confidence: 99%